2020
DOI: 10.12691/jfnr-8-9-2
|View full text |Cite
|
Sign up to set email alerts
|

<i>Nelumbo nucifera</i> Leaf Extracts Inhibit Melanogenesis in B16 Melanoma Cells and Guinea Pigs through Downregulation of CREB/MITF Activation

Abstract: Nelumbo nucifera leaves extracts (NLE) has been suggested to provide antioxidant, anti-obesity and anticancer effects. However, the research on the anti-melanogenetic effect of NLE was little. Here, we reported that NLE and Gallic acid (GA, major ingredients of NLE) exhibit the hypopigmentary effect in B16F1 cells. NLE and GA showed potent inhibitory effects on tyrosinase, microphthalmia-associated transcription factor (MITF), and tyrosinase-related protein-1 (TRP-1) protein production. The phosphorylation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Mechanistic studies using an immunoblotting assay revealed that both treatments reduced the expressions of tyrosinase, microphthalmia-associated transcription factor (MITF), TRP-1, phosphorylated protein kinase A (p-PKA), and phosphorylated cAMP response element-binding protein (p-CREB) (Lai et al, 2020). In another study, Liu et al [138] demonstrated that 7hydroxydehydronuciferine, a compound isolated from a methanolic extract of the leaves of N. nucifera Gaertn. cv.…”
Section: Skin Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanistic studies using an immunoblotting assay revealed that both treatments reduced the expressions of tyrosinase, microphthalmia-associated transcription factor (MITF), TRP-1, phosphorylated protein kinase A (p-PKA), and phosphorylated cAMP response element-binding protein (p-CREB) (Lai et al, 2020). In another study, Liu et al [138] demonstrated that 7hydroxydehydronuciferine, a compound isolated from a methanolic extract of the leaves of N. nucifera Gaertn. cv.…”
Section: Skin Cancermentioning
confidence: 99%
“…The mice treated with the procyanidin-rich extract also displayed an increased spleen and thymus index, indicating immunomodulatory activities. Lai et al [138] also conducted an in vivo study using ultra-violet B (UVB)-radiation exposed female guinea pigs and topically treated them with 1-2% NLE. The test agent was found to reverse UVB-induced epidermal hyperplasia and decrease melanin content, as evidenced by hematoxylin and eosin staining and Fontana-Masson staining, respectively.…”
Section: Skin Cancermentioning
confidence: 99%
“…Moreover, CREB was activated by cirsimaritin, a dimethoxyflavone, isolated from the branches of Lithocarpus dealbatus [ 101 ], hesperetin, a flavanone glycoside, from Citrus sinensis , Citrus aurantium and Citrus reticulata extract [ 102 ] and scopoletin, a hydroxycoumarin, from the aerial parts of Cirsium setidens [ 103 ]. The opposite effect on phosphorylation of PKA and CREB are interfered with by Nelumbo nucifera leaf extract [ 104 ]. Rhodiola rosea root extract [ 105 ], Elaeagnus umbellate branches and leaves [ 106 ], Oenothera laciniata extracts [ 107 ] and Kadsura coccinea roots, stems, leaves, fruits [ 108 ] extracts inhibited the phosphorylation of CREB followed by downregulation of MITF and TYR expression.…”
Section: Mechanisms Of Melanogenesis-related Signaling Pathway Modula...mentioning
confidence: 99%
“…Nelumbo nucifera extract, used at 1% or 2% concentration and administered to UVB-irradiated guinea pigs on the back region for 2 weeks demonstrates similar activity. The main identified constituent was gallic acid [ 106 ]. Data show that 200 μL of Nymphaea nouchali extract, applied on UVB-irradiated HRM-2 hairless mice at a concentration 100 µg/mL to a 3 cm × 3 cm designated area on the dorsal skin for 4 weeks exhibit antimelanogenic effects [ 107 ].…”
Section: The Effect Of Plant Extracts and Pure Compounds On Melanin C...mentioning
confidence: 99%
“…The first one exerts an anti-melanogenic effect, whereas the other one-melanogenic effect. Regulation of cAMP/CREB/MAPKs/MITF and PKA/CREB/MITF axis and suppression of melanogenesis takes place by Nymphaea nouchali [ 107 ] and Nelumbo nucifera [ 106 ] extracts. Pueraria montana var.…”
Section: In Vitro Studiesmentioning
confidence: 99%